Wavelet based ECG compression with X-tree coding scheme and weighted diagnostic distortion measure - Subhashis Swain. (2008)
Modern clinical systems require the storage and transmission of large quantities of ECG signals. Efficient data compression is needed in order to reduce these quantities of data. In ECG signal compression algorithms, the aim is to achieve minimum compression rate, while keeping the relevant diagnostic information in the reconstructed signal.